Taxa de ocupação da jaguatirica (Leopardus pardalis) e segregação espacial e temporal de felídeos na região norte e nordeste do Estado de São Paulo - Fornitano, Larissa [UNESP] (2015)
The spatial distribution and occurrence of species in the landscape are influenced by environmental conditions and the availability resources. Hábitat fragmentation can cause the reduction or elimination of these resources leading to the decline or disappearance of populations and species. Some interactions such as predation and competition can also be factors influencing species distribution; these interactions may be intensified between related species and may adversely affect species distribution and abundance. The aims of this study were to evaluate occupancy rate of ocelot (Leopardus pardalis), the relative abundance index and competitive relations of the ocelot, the jaguarundi (Puma yagouaroundi) and puma (Puma concolor) in the northern of São Paulo state. Camera traps were used from October/2012 to January/2015 in three protected areas of north and northeast state. The ocelot's occupancy rate in Jataí Ecological Station indicated a higher likelihood of species occupation in locations close to roads and showing higher biomass of prey, and a lower probability of occupying places nearly water courses. In State Park Furnas do Bom Jesus we observed a negative association of the puma with the ocelot and the jaguarundi, and a positive association between the ocelot and the jaguarundi; there was no overlaps of activity time between the ocelot and the jaguarundi, while the puma and ocelot co-occurred temporally. In Jataí Ecological Station, the ocelot and puma were positively associated and co-occurred temporally...